Contextualizing the Star-shaped Lamps in the Levant - Rosenthal-Heginbottom, Renate (Journal of Hellenistic Pottery and Material Culture, 2021)
In the eastern Mediterranean wheel-made and moldmade multi-nozzle lamps represent a small, yet conspicuous category. Of particular interest is a category of star-shaped lamps with seven nozzles, found in the southern Levant at coastal sites, on the Golan Hights, in the Decapolis and in Idumea, with sporadic examples from Delos and Ras Ihn Hani in northern Syria. The sites have a predominantly gentile population of diverse ethnicity. To date, no lamps have been recorded in Hasmonean Judea and in Nabatea, and no workshops have been identified. The prevalent lamps with incuse chevron patterns (cat. nos. 10–26) display differences in the execution of the morphological features and of the ornamentation, suggesting the hands of several artisans and craftsmen. There is no explicit conformity to assign lamps to the same workshop.